FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA INTELECTUAL CAPITAL PADA INDUSTRI PERBANKAN YANG LISTING DI BURSA EFEK INDONESIA - Widaryanti . (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2011)
The purpose of this paper is to investigate the determinants of intellectual capital performance in Indonesian banks who listed in Indonesian Stock Exchange over the period 2006-2008. Multiple regression analysis is used to test the relationship between the intellectual capital performance as a dependent variable and certain independent variables are bank profitability, efficiency of investment in intellectual capital, barriers to entry, bank efficiency. Results indicate that the standard variables, bank profitability and bank risk, are important. The results also show that investment in information technology (IT) systems, bank efficiency, barriers to entry and efficiency of investment in intellectual capital variables, which have not been considered in previous studies, have a significant impact on intellectual capital performance.The study might help the banking regulators in addressing the factors affecting intellectual capital performance to take actions towards developing their performance and in turn maximise their value creation. This paper adds to the literature on the determinants of intellectual capital performance in banks. In particular, it tests the theories that investment in IT systems, bank efficiency, barriers to entry and efficiency of investment in intellectual capital have impact on intellectual capital performance.